(3-4a)(7-5a)=

Simple and best practice solution for (3-4a)(7-5a)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3-4a)(7-5a)= equation:


Simplifying
(3 + -4a)(7 + -5a) = 0

Multiply (3 + -4a) * (7 + -5a)
(3(7 + -5a) + -4a * (7 + -5a)) = 0
((7 * 3 + -5a * 3) + -4a * (7 + -5a)) = 0
((21 + -15a) + -4a * (7 + -5a)) = 0
(21 + -15a + (7 * -4a + -5a * -4a)) = 0
(21 + -15a + (-28a + 20a2)) = 0

Combine like terms: -15a + -28a = -43a
(21 + -43a + 20a2) = 0

Solving
21 + -43a + 20a2 = 0

Solving for variable 'a'.

Factor a trinomial.
(3 + -4a)(7 + -5a) = 0

Subproblem 1

Set the factor '(3 + -4a)' equal to zero and attempt to solve: Simplifying 3 + -4a = 0 Solving 3 + -4a = 0 Move all terms containing a to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -4a = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -4a = 0 + -3 -4a = 0 + -3 Combine like terms: 0 + -3 = -3 -4a = -3 Divide each side by '-4'. a = 0.75 Simplifying a = 0.75

Subproblem 2

Set the factor '(7 + -5a)' equal to zero and attempt to solve: Simplifying 7 + -5a = 0 Solving 7 + -5a = 0 Move all terms containing a to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -5a = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -5a = 0 + -7 -5a = 0 + -7 Combine like terms: 0 + -7 = -7 -5a = -7 Divide each side by '-5'. a = 1.4 Simplifying a = 1.4

Solution

a = {0.75, 1.4}

See similar equations:

| 2.25x+1.25t=13.50 | | 4(2)(g)+4(9)30=109 | | 5-2[6-(8y-2)]= | | -12+9x=7x+18 | | 2x+3-4X+1=6 | | 9y-2(3y-30)=y+80 | | 38+2a+54= | | 2(x+50)-6=4(3x+20) | | 18-25n=10 | | 41000000+b=56000000 | | 5-2x=19-5x | | 2x-4=2x+-2 | | x^2+(x-2)(x-2)=(x-9)(x-9) | | 15x-8=4x+47 | | (3t-2)+6=2 | | 11x+33= | | 7y+x=37 | | 3m-60+3m=2m+84 | | 3x+5y-2x-7y= | | x+3*2x=90 | | 5(5)(g)+5(3)+25=115 | | 7(3+4x)=21 | | 4x-44=4(5x+1) | | 3(c-8)=c+76 | | 3x-2(x-3)=4-(5x-1) | | 47.90=0.045k+6.5 | | 6-6x=6x-10x-6 | | 6+x=4.25 | | 3.14159265359=7x-2y | | 2h^2-2h-1=0 | | 2(6-x)=8 | | -3x-82=8x+50 |

Equations solver categories